Mini table saw project / Muhammad Hazim Irfan Kamaruzaman - Kamaruzaman, Muhammad Hazim Irfan (2023)
The mini table saw is often referred to as the wood shop’s workhorse since it is the most flexible and prolific of all woodworking machines. The problem facing by many small workshop owner and local carpenter Is that in order to cut single piece of wood they have to use bigger expensive table saw. As a result, more electricity is consumed and more room is acquired. The objective of this project is to perform essential cut quickly, safely and efficiently. It also to cut work piece precisely in required dimension. Next, to reduce the power consumption of electricity usage. The methodologies used in this project is 12V-24V dc motor, circular saw blade, base frame and screws. The expected result for this project is should be can cut small work piece wisely